APLIKASI PENGAWASAN DAN PENGADUAN PADA DINAS LINGKUNGAN HIDUP KOTA JAMBI: APPLICATION OF COMPLAINTS AND SUPERVISION ON WEB-BASED, COMMUNITY, GOVERNMENT, ENVIRONMENT AGENCY. - Purnama, Fery; Irawan (FORTECH (Journal of Information Technology), 2019)
Researchers are interested in taking the title of the thesis "Application of Surveillance and Complaints to the Jambi City Environmental Service" due to the advancement of current technological developments needed by an information system that can support the development and progress in fulfilling information related to complaints and public oversight of the Jambi City Environment. The purpose of this design is to produce a complaint and supervision application that can facilitate complaints and supervision and help the government to monitor the complaints process and supervision. Researchers use analysis (interviews and literature studies). The concepts used in this study are complaints and public supervision, website-based online. The results achieved in making this complaint and monitoring application is to facilitate the complaints and supervision process for the people who live far from the Jambi City Environmental Service Office and make it easier for office staff to collect every complaint and supervision which will then be processed. Conclusions from the making of this application are the complaints process and supervision of the Jambi city government which will be processed by the admin can be streamlined by using the complaint application to the environment office of Jambi City.